Transcranial focused ultrasound stimulation in the infralimbic cortex facilitates extinction of conditioned fear in rats - Jaeyong Lee; Ye Eun Kim; Jihong Lim; Yehhyun Jo; Hyunjoo Jenny Lee; Yong Sang Jo; June-Seek Choi (Brain Stimulation, 2024)
Transcranial focused ultrasound (tFUS) neuromodulation emerges as a promising non-invasive approach for improving neurological conditions. Extinction of conditioned fear has served as a prime model for exposure-based therapies for anxiety disorders. We investigated whether tFUS stimulation to a critical brain area, the infralimbic subdivision of the prefrontal cortex (IL), could facilitate fear extinction using rats. In a series of experiments, tFUS was delivered to the IL of a freely-moving rat and compared to sham stimulation (tFUS vs. SHAM). Initially, Fos expression in the IL was measured shortly after the stimulation. The results show that Fos expression was significantly increased in the IL but not in the neighboring regions compared to SHAM. Subsequently, two groups of rats were subjected to fear conditioning, extinction, and retention while receiving stimulation during the extinction. Rats in the tFUS group froze significantly less than SHAM during both extinction and retention tests. Importantly, the reduced freezing in the tFUS group was not attributable to non-specific effect such as auditory noise, as both groups demonstrated a similar level of locomotive activity in an open field regardless of the stimulation condition. Finally, we replicated the procedure with a shortened conditioning-to-extinction interval (15 min) to induce immediate extinction deficit. The tFUS group showed a facilitated reduction in freezing during the extinction, which persisted in the subsequent retention session compared to SHAM. In summary, the current findings suggest that tFUS stimulation in the IL facilitates fear extinction, offering a potential therapeutic regimen for fear-related psychiatric disorders.